Time course of changes in heart rate and blood pressure variability in rats with myocardial infarction - Aires,R. (2017)
Our aim was to determine the time course of changes in autonomic balance in the acute (1 and 3 days), sub-acute (7 days) and chronic (28 days) phases of myocardial infarction (MI) in rats. Autonomic balance was assessed by temporal and spectral analyses of blood pressure variability (BPV) and heart rate variability (HRV). Pulsatile blood pressure (BP) recordings (30 min) were obtained in awake and unrestrained male Wistar rats (N = 77; 8-10 weeks old) with MI (coronary ligature) or sham operation (SO). Data are reported as means±SE. The high frequency (HF) component (n.u.) of HRV was significantly lower in MI-1- (P<0.01) and MI-3-day rats (P<0.05) than in their time-control groups (SO-1=68±4 vs MI-1=35.3±4.3; SO-3=71±5.8 vs MI-3=45.2±3.8), without differences thereafter (SO-7=69.2±4.8 vs MI-7=56±5.8; SO-28=73±4 vs MI-28=66±6.6). A sharp reduction (P<0.05) of BPV (mmHg2) was observed in the first week after MI (SO-1=8.55±0.80; SO-3=9.11±1.08; SO-7=7.92±1.10 vs MI-1=5.63±0.73; MI-3=5.93±0.30; MI-7=5.30±0.25). Normal BPV, however, was observed 4 weeks after MI (SO-28=8.60±0.66 vs MI-28=8.43±0.56 mmHg2; P>0.05). This reduction was mainly due to attenuation of the low frequency (LF) band of BPV in absolute and normalized units (SO-1=39.3±7%; SO-3=55±4.5%; SO-7=46.8±4.5%; SO-28=45.7±5%; MI-1=13±3.5%; MI-3=35±4.7%; MI-7=25±2.8%; MI-28=21.4±2.8%). The results suggest that the reduction in HRV was associated with decrease of the HF component of HRV suggesting recovery of the vagal control of heartbeats along the post-infarction healing period. The depression of BPV was more dependent on the attenuation of the LF component, which is linked to the baroreflex modulation of the autonomic balance.